p Faktor Signal Dan Agency Dalam Mempengaruhi Nilai Perusahaan Di Jakarta Islamic Index - Jayanti, Citra Meilana Rina; Mashudi; Muhamad Aswad (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2024)
This research uses a quantitative approach that focuses on the influence of leverage, Investment Opportunity Set, managerial ownership, institutional ownership on company value with profitability as an intervening variable in companies listed in the Jakarta Islamic Index. This type of research uses associative research with 50 data samples. The data collection tool is the company's annual financial report and uses the Sobel test analysis path with the Eviews 10 statistical program. The results of this research show that: Leverage, Investment opportunity set, Institutional ownership, Profitability, have a significant effect on company value. while managerial ownership, leverage, investment opportunity, managerial ownership, institutional ownership do not have a significant effect on company value.